If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -5)(3x) = 0 Reorder the terms: (-5 + 4x)(3x) = 0 Remove parenthesis around (3x) (-5 + 4x) * 3x = 0 Reorder the terms for easier multiplication: 3x(-5 + 4x) = 0 (-5 * 3x + 4x * 3x) = 0 (-15x + 12x2) = 0 Solving -15x + 12x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3x'. 3x(-5 + 4x) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-5 + 4x)' equal to zero and attempt to solve: Simplifying -5 + 4x = 0 Solving -5 + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 4x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 4x = 0 + 5 4x = 0 + 5 Combine like terms: 0 + 5 = 5 4x = 5 Divide each side by '4'. x = 1.25 Simplifying x = 1.25Solution
x = {0, 1.25}
| 325-x+650-2x+x=875 | | 4[6-(1+2x)]+10x=2(10x-3)+8x | | ln(3.59)=x | | -8x+12=15x-14 | | 8x+12y=50fory | | 5x+3a=5b | | 555+666x-3*x=534 | | 10t+2=2-7 | | 8-2x-5x-13=0 | | 2x+14=18y | | 2y+14=22x | | 2x+14=22y | | 0.7(7x+14)=1.1-(x+2) | | 91-(5x+16)=5(x+4)+x | | 36-(2x+5)=2(x+8)+x | | 4x-10-1x+3=14 | | 12.5/x=75/600 | | -1/4y-1=14.5 | | a^4b^-3/(a^2b^-3)^-2 | | -1/4y-1=14 | | 3n-10=6n-20 | | 5(b-x)=a(x-2) | | -2*2n+3=8 | | 4*x-2-12=0 | | 7y-2y-84=2y-2y+61 | | (3a+b)-bx=a(x-2) | | N^3-6n^2-4n+24=0 | | 9x-(4x-10)=50 | | 27r^3+125=0 | | 16z^2-40z+25=0 | | ((100x^2)/16)-(4y/49) | | 156.25+5.75x=7x |